POLITIK PENGELOLAAN KARST SANGKULIRANG- MANGKALIHAT: NONGOVERNMENTAL ORGANIZATION DAN AGENDA KELESTARIAN LINGKUNGAN - Etha Pasan (Universitas Jenderal Ahmad Yani, 2019)
This research try to describe how local NGO in East Kalimantan, Jatam (Mining Advocacy Network) and Walhi (Friends of the Life) pursue their interest in the politics of environmental management in Sangkulirang-Mangkalihat Karst Area in East Kutai and Berau Regency in East Kalimantan Province. How do they strive for their interest? What kind of strategy they deploy? And why? The result shows that there are several strategies that Jatam and Walhi use. They are: 1) Protest, 2) Seminar/FGD, and 3) Campaign. Those strategies are influenced by internal and external factors. For the internal factors, both Jatam and Walhi’s structure of organization creates possibilities to collaborate with other party with the same agenda to achieve the goal. The second internal factor is the funding. Is is widely known that local NGO in East Kalimantan, especially those who strive for environmental protection lack the financial resources to fund their agenda. Both Jatam and Walhi’s financial resources are relatively small compared to the resources of related actors such as the Government and corporations. With such conditions, street protests, seminar and campaign become the rational instruments to be deployed. The last is external factor that considers the social and political context of East Kalimantan society that make them choose those strategies.